Bacteriological profile and its antibiotic susceptibility in patients with Urinary Tract Infection in a diagnostic center in Dhaka - Islam, Namista (BRAC Univeristy, 2018)
This thesis report is submitted in partial fulfilment of the requirement for the degree of B.Sc in Microbiology, 2018.